Anaphylaxis fatalities and admissions in Australia - Liew, Woei Kang; Williamson, Elizabeth; Tang, Mimi L.K. (Journal of allergy and clinical immunology, 2009)
Detailed data on fatal anaphylaxis are limited, with national anaphylaxis fatality data for the United Kingdom and food-induced anaphylaxis fatality data for the United States. Time trends for anaphylaxis fatalities are not available. We examined causes, demographics, and time trends for anaphylaxis fatalities in Australia between January 1997 and December 2005 and compared these with findings for anaphylaxis admissions. Data on anaphylaxis deaths and hospital admissions were extracted from a national database. Death certificate codes were analyzed to determine the likely cause and associated comorbidities. There were 112 anaphylaxis fatalities in Australia over 9 years. Causes were as follows: food, 7 (6%); drugs, 22 (20%); probable drugs, 42 (38%); insect stings, 20 (18%); undetermined, 15 (13%); and other, 6 (5%). All food-induced anaphylaxis fatalities occurred between 8 and 35 years of age with female preponderance, despite the majority of food-induced anaphylaxis admissions occurring in children less than 5 years of age. Most insect sting–induced anaphylaxis deaths occurred between 35 and 84 years almost exclusively in male subjects, although bee sting–induced admissions peak between 5 and 9 years of age with a male/female ratio of 2.7. However, most drug-induced anaphylaxis deaths occurred between 55 and 85 years with equal sex distribution similar to drug-induced anaphylaxis admissions. There was no evidence of an increase in death rates for food-induced anaphylaxis, despite food-induced anaphylaxis admissions increasing approximately 350%. In contrast, drug-induced anaphylaxis deaths increased approximately 300% compared with an approximately 150% increase in drug-induced anaphylaxis admissions. The demographics for anaphylaxis deaths are different to those for anaphylaxis presentations. Anaphylaxis mortality rates remain low and stable, despite increasing anaphylaxis prevalence, with the exception of drug-induced anaphylaxis deaths, which have increased.